Ethernet connectivity and flexible Iot for monitoring machining processes in Cnc machines - Barros, Matheus Bailão de; Fonseca, João Paulo da Silva (Brazilian Journal of Production Engineering, 2024)
This study investigates the application of Ethernet connectivity in CNC machines, aiming to simplify the visualization of data from various sources. The main focus lies in designing a connection architecture that enables seamless integration between a ROMI D600 Machining Center, a ROMI GL 240 CNC lathe, and a central computer. This integrated architecture not only generated and presented real-time operational data from the machines but also provided a set of interactive dashboards. The results concretely validate the benefits offered by the implementation of Industry 4.0 technologies in manufacturing systems, demonstrating the effectiveness of the proposed approach in facilitating the ability for instant analysis of operations across multiple devices..
Keywords: Industry 4.0; Internet of Things; Monitoring; CNC; Ethernet